Creating meaningful data from web logs for improving the impressiveness of a website by using path analysis method - Das, Resul; Turkoglu, Ibrahim (Pergamon-Elsevier Science Ltd, 2009)
Web usage mining is to analyze web log files to discover user accessing patterns of web pages. in order to effectively manage and report on a website, it is necessary to get feedback about activity on the web servers. The aim of this study is to help the web designer and web administrator to improve the impressiveness of a website by determining occurred link connections on the website. Therefore, web log files are pre-processed and then path analysis technique is used to investigate the URL information concerning access to electronic Sources. The proposed methodology is applied to the web log files in the web server of Firat University. The results and findings of this experimental study can be used by the web designer in order to plan the upgrading and enhancement to the website. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Web mining; Web usage mining; Web log files; Path analysis